2020
DOI: 10.20517/2394-5079.2019.51
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of hepatocellular carcinoma following deceased donor liver transplantation: case series

Abstract: Aim: We aimed to study the clinical and pathological characteristics of liver transplant recipients with hepatocellular carcinoma recurrence. Methods: We reviewed the data for 26 patients who had tumor recurrence after deceased donor liver transplant for hepatocellular carcinoma at the Johns Hopkins Hospital from January 2005 to December 2015. Results: In total, 88% of recipients were males. The mean age was 59 years. On explant, poor differentiation was detected in 43%, while 73% had microvascular invasion. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…A recent case series showed that approximately one-third of patients were within MC on explant pathology when they were all within MC according to imaging findings. 111 Other factors such as vascular invasion, degree of tumor differentiation, tumor stage and AFP levels also play an important role in recurrence. The OS after HCC recurrence is approximately 1 year.…”
Section: Recurrence After Transplantmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent case series showed that approximately one-third of patients were within MC on explant pathology when they were all within MC according to imaging findings. 111 Other factors such as vascular invasion, degree of tumor differentiation, tumor stage and AFP levels also play an important role in recurrence. The OS after HCC recurrence is approximately 1 year.…”
Section: Recurrence After Transplantmentioning
confidence: 99%
“…At our center, postoperative HCC surveillance usually consists of contrasted cross-sectional imaging with CT or MRI with AFP measurement every 3 months for the first year and every 6 months for the second and third years. 111 …”
Section: Post-transplant Surveillancementioning
confidence: 99%